RETRACTED: Hypertonic Saline Compared to Mannitol for the Management of Elevated Intracranial Pressure in Traumatic Brain Injury: A Meta-Analysis - Han, Chengchen; Yang, Fan; Guo, Shengli; Zhang, Jianning (Frontiers in Surgery, 2022)
Background We performed a meta-analysis to evaluate the effect of hypertonic saline compared to mannitol for the management of elevated intracranial pressure in traumatic brain injury. Methods A systematic literature search up to July 2021 was performed and 7 studies included 1392 subjects with traumatic brain injury at the start of the study; 708 of them were administered hypertonic saline and 684 were given mannitol. They were reporting relationships between the effects of hypertonic saline compared to mannitol for the management of elevated intracranial pressure in traumatic brain injury. We calculated the odds ratio (OR) and mean difference (MD) with 95% confidence intervals (CIs) to assess the effect of hypertonic saline compared to mannitol for the management of elevated intracranial pressure in traumatic brain injury using the dichotomous or continuous method with a random or fixed-effect model. Results Hypertonic saline had significantly lower treatment failure (OR, 0.38; 95% CI, 0.15–0.98, p =0.04), lower intracranial pressure 30-60 minutes after infusion termination (MD, -1.12; 95% CI, -2.11– -0.12, p =0.03), and higher cerebral perfusion pressure 30-60 minutes after infusion termination (MD, 5.25; 95% CI, 3.59–6.91, p < 0.001) compared to mannitol in subjects with traumatic brain injury. However, hypertonic saline had no significant effect on favorable outcome (OR, 1.61; 95% CI, 1.01–2.58, p = 0.05), mortality (OR, 0.59; 95% CI, 0.34–1.02, p = 0.06), intracranial pressure 90-120 minutes after infusion termination (MD, -0.90; 95% CI, -3.21–1.41, p =0.45), cerebral perfusion pressure 90-120 minutes after infusion termination (MD, 4.28; 95% CI, -0.16–8.72, p = 0.06), and duration of elevated intracranial pressure per day (MD, 2.20; 95% CI, -5.44–1.05, p = 0.18) compared to mannitol in subjects with traumatic brain injury. Conclusions Hypertonic saline had-significantly-lower-treatment-failure,-lower-intracranial-pressure-30-60-minutes-after-infusion-termination,-and-higher-cerebral-perfusion-pressure-30-60-minutes-after-infusion-termination compared to mannitol in subjects with traumatic brain injury. However, hypertonic saline had no significant effect on the favorable outcome, mortality, intracranial pressure 90-120 minutes after infusion termination, cerebral perfusion pressure 90-120 minutes after infusion termination and duration of elevated intracranial pressure per day compared to mannitol in subjects with traumatic brain injury. Furthers studies are required to validate these findings.